Millennial Alumni Perceptions of Communications: A Look at One Land Grant University’s Media Use - Amanda Northfell; Leslie D. Edgar; Donna L. Graham; K. Jill Rucker (Journal of Applied Communications, 2016)
An important aspect of higher education is alumni relationship cultivation, because it keeps alma maters connected to graduates. To assess this relationship, researchers sought to describe Millennial alumni perceptions of media distributed by the Dale Bumpers College of Agricultural, Food, and Life Sciences (Bumpers College) from 2012 through 2014. Assessed media included alumni magazines, an e-newsletter, key event invitations, College website, and social media presences. Active and inactive alumni responses were gathered via telephone interviews and qualitatively analyzed for emergent themes. Researchers identified Building the Professional and Interest in Giving Back as themes related to respondents’ connection to Bumpers College. Five additional themes emerged related to assessed media and included Message Relationship, Specialized Content, Communications Medium, Message Barriers, and Need for Promotion. No alumni were dissatisfied with their collegiate experience and favored monetary donations for its convenience. Alumni sought a personable-angle communications media and were drawn by updates about the College’s research and global impacts. Respondents consumed print and digital media differently with engagement based on personal preference and flexibility. Subthemes emerged related to Message Barriers and included time, distance, vague messages, too much information, non-relatable subject matter, technical errors, and outdated information. Finally, there was little brand recognition between Bumpers College and University messaging, and most alumni were unaware of the College’s social media presences.
Keywords: Agricultural Communications; Agricultural Education; Alumni Relations; Communications; Development; Higher Education; Media; Millennial Alumni